Inovasi TAMPAYANG sebagai Alat Pemurnian Air Laut di Desa Pulau Ay Kecamatan Banda Kabupaten Maluku Tengah - Farida Bahalwan; Wa Nirmala; Kasliyanto Kasliyanto (Jurnal Penelitian Pendidikan IPA, 2022)
Pulau Ay is an island located west of the Banda Islands, Central Maluku Regency, Maluku Province. Nearly 85% of the soil structure on Ay Island is filled with coral reefs, so it is very difficult to get clean water and the people of Ay Island only rely on rainwater to get clean water. The purpose of this research is to innovate to purify seawater into drinking water in the village of Pulau Ay and test the quality of the water produced. This research was conducted by designing a seawater purification device called Tampayang (Ay Island's drinking water station) consisting of a water storage barrel, a simple filter, a seawater distillation apparatus and a reverse osmosis (RO) membrane machine. The water produced from the purification of seawater is then analyzed in a laboratory according to Indonesian national standard and the regulation of the Minister of Health of 2010 concerning drinking water quality requirements. The results showed that the Tampayang tool produces 2 types of water, namely clean water and drinking water. After being tested both types of water meet the water quality requirements for consumption based on physical, chemical and biological parameters. The clean water and drinking water produced can be useful and consumed by the people of Ay Island as a solution to seawater utilization